Enhancing Gambir's Economic Value from Processing to Bath Soap Raw Materials: Community Service Program - Uswatul Hasanah; Nova Syafni; Adhitya Jessica; Erizal Zaini; Rini Agustin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Gambir, an extract derived from the leaves and branches of the gambir plant, holds significant potential for enhancing the local economy and its benefits as a cosmetics product. Jorong Balai Tampuak Pinang, Nagari Simpang Kapuak, Kecamatan Mungka, was one of the areas producing traditional gambir in Lima Puluh Kota district, West Sumatra, Indonesia. This community service initiative aimed to augment the economic value of gambir from its processing to raw materials of bath soap. The initiative began with an educational session for training participants, outlining the advantages of gambir in skincare and how to incorporate it into bath soap formulations. Following the learning session, participants actively produced gambir-contained bath soap utilizing the provided formula. The activity received favorable feedback from participants who appreciated enhancing knowledge and skills. The outcomes of this endeavor underscore the substantial potential of developing body care products utilizing gambir as a primary ingredient. Participant testimonials underscore the need to conduct similar community engagement activities to harness Gambir's further utilization of other personal care products. The collaboration between the pharmacy study program and the local community has opened new avenues for local economic development and sustainable growth, significantly impacting the local population's well-being in the region.